Аналіз показників якості лабораторної інформаційної систем та їх вплив на показники оцінювання ефективності IT-проєктів при її впровадженні або модернізації - Веретельніков, Д. М. (ХНУРЕ, 2024)
This investigation explores the interconnection between quality indicators of Laboratory Information Systems (LIS) and the evaluation metrics of IT projects, focusing on its introduction or modernization processes. By carefully examining and combining relevant information, the research helps us understand the complex relation between how well LIS perform and how effective IT projects are overall. The results show that it's important to match the quality of LIS with the goals of the project. This suggests that focusing on the quality of LIS during their introduction or modernization can improve the results of projects. This study gives us a better understanding, how LIS quality affects the success of IT projects, providing useful knowledge for those who work with healthcare projects.
Keywords: IT-проєкт; інформаційна система